Clarifying Nursing as a Discipline: The Case for Nursology - Cyruz Tuppal (Caring: Indonesian Journal of Nursing Science, 2026)
Nursing science has developed into a multifaceted field that integrates empirical, theoretical, and humanistic knowledge. Despite its intellectual development, questions remain regarding the conceptual clarity of its disciplinary identity, which is often positioned as an applied health science rather than an autonomous field of inquiry. In response to these ongoing debates, nursology has been proposed as a conceptual reframing that seeks to articulate the ontological, epistemological, and methodological foundations of nursing more explicitly. This paper aims to explore the conceptual and philosophical basis of nursology as a proposed disciplinary reframing of nursing science through philosophical inquiry and theoretical synthesis. A philosophical–theoretical approach was employed using conceptual analysis, disciplinary critique, and integrative synthesis. Canonical works in philosophy of science, phenomenology, hermeneutics, ethics, and caring science were critically examined to explore the conceptual foundations of nursology. The analysis identified four interrelated conceptual dimensions disciplinary differentiation, caring ontology, epistemological coherence, and methodological pluralism that collectively provide a philosophical framework for understanding nursology as a proposed conceptual orientation for nursing science rather than as an empirically established independent discipline. This paper argues that nursology may offer a coherent philosophical framework for clarifying nursing's disciplinary identity and strengthening the theoretical integration of research, education, and practice. Further scholarly dialogue and empirical inquiry are warranted to examine the usefulness and applicability of this conceptual perspective. Keywords: Caring Ontology, Integrative Epistemology, Methodological Pluralism, Nursology, Nursing Science